Carbon reduction and hygrothermal performance of mid- and high-rise hybrid CLT buildings as residential apartments - Yujin Kang; Sumin Kim (Case Studies in Thermal Engineering, 2025)
Evaluating the thermal performance and carbon reduction potential of hybrid cross-laminated timber (CLT) buildings for mid-to high-rise residential apartments in the Korean climate, this case analysis considers the impact of building shapes and insulation materials on energy demand, indoor comfort, and carbon efficiency. Hygrothermal simulations revealed that CLT walls block outdoor moisture but are vulnerable to indoor moisture under high-humidity conditions, requiring surface treatments. Hybrid CLT walls offered better insulation than reinforced concrete (RC) walls; however, energy savings were minimal owing to the high thermal mass of RC. Cooling demand, driven by solar heat gain through large south-facing windows, exceeded heating demand. Life cycle assessment (LCA) indicated that hybrid CLT buildings could achieve carbon savings of up to 135.9 tCO2-eq over 40 years. Designs using phenolic foam (PF) insulation showed the greatest reductions in embodied carbon compared to polyurethane insulation (PIR). Additional carbon savings could be realized by extending CLT usage to floors and core walls while ensuring structural integrity. Hybrid CLT construction offers a viable low-carbon, energy-efficient solution for residential buildings in Korea, providing moisture safety and significant GHG reductions. Addressing challenges such as timber supply and manufacturing capacity is essential for wider adoption.